A Search for Novel Legionella pneumophila Effector Proteins Reveals a Strain Specific Nucleotropic Effector - Monteiro, Inês P.; Sousa, Sofia; Borges, Vítor; Gonçalves, Paulo; Gomes, João Paulo; Mota, Luís Jaime; Franco, Irina S. (Frontiers in Cellular and Infection Microbiology, 2022)
Legionella pneumophila is an accidental human pathogen that causes the potentially fatal Legionnaires’ disease, a severe type of pneumonia. The main virulence mechanism of L. pneumophila is a Type 4B Secretion System (T4SS) named Icm/Dot that transports effector proteins into the host cell cytosol. The concerted action of effectors on several host cell processes leads to the formation of an intracellular Legionella-containing vacuole that is replication competent and avoids phagolysosomal degradation. To date over 300 Icm/Dot substrates have been identified. In this study, we searched the genome of a L. pneumophila strain (Pt/VFX2014) responsible for the second largest L. pneumophila outbreak worldwide (in Vila Franca de Xira, Portugal, in 2014) for genes encoding potential novel Icm/Dot substrates. This strain Pt/VFX2014 belongs to serogroup 1 but phylogenetically segregates from all other serogroup 1 strains previously sequenced, displaying a unique mosaic genetic backbone. The ability of the selected putative effectors to be delivered into host cells by the T4SS was confirmed using the TEM-1 β-lactamase reporter assay. Two previously unknown Icm/Dot effectors were identified, VFX05045 and VFX10045, whose homologs Lpp1450 and Lpp3070 in clinical strain L. pneumophila Paris were also confirmed as T4SS substrates. After delivery into the host cell cytosol, homologs VFX05045/Lpp1450 remained diffused in the cell, similarly to Lpp3070. In contrast, VFX10045 localized to the host cell nucleus. To understand how VFX10045 and Lpp3070 (94% of identity at amino acid level) are directed to distinct sites, we carried out a comprehensive site-directed mutagenesis followed by analyses of the subcellular localization of the mutant proteins. This led to the delineation of region in the C-terminal part (residues 380 to 534) of the 583 amino acid-long VFX10045 as necessary and sufficient for nuclear targeting and highlighted the fundamental function of the VFX10045-specific R440 and I441 residues in this process. These studies revealed a strain-specific nucleotropism for new effector VFX10045/Lpp3070, which anticipates distinct functions between these homologs.